Steps to solve:
3(x - 1) = 5x + 3 - 2x
~Distribute left side
3x - 3 = 5x + 3 - 2x
~Combine like terms
3x - 3 = 3x - 3
~Subtract 3x to both sides
-3 = -3
~Add 3 to both sides
0 = 0
All real numbers are solutions.
Best of Luck!
Answer:yes
Step-by-step explanation:
<BAC=<BDE
<BCA=BED
Answer:
20
Step-by-step explanation:
Simply divide 8 by 0.4 to get 20
Answer:
(i) (f - g)(x) = x² + 2·x + 1
(ii) (f + g)(x) = x² + 4·x + 3
(iii) (f·g)(x) = x³ + 4·x² + 5·x + 2
Step-by-step explanation:
The given functions are;
f(x) = x² + 3·x + 2
g(x) = x + 1
(i) (f - g)(x) = f(x) - g(x)
∴ (f - g)(x) = x² + 3·x + 2 - (x + 1) = x² + 3·x + 2 - x - 1 = x² + 2·x + 1
(f - g)(x) = x² + 2·x + 1
(ii) (f + g)(x) = f(x) + g(x)
∴ (f + g)(x) = x² + 3·x + 2 + (x + 1) = x² + 3·x + 2 + x + 1 = x² + 4·x + 3
(f + g)(x) = x² + 4·x + 3
(iii) (f·g)(x) = f(x) × g(x)
∴ (f·g)(x) = (x² + 3·x + 2) × (x + 1) = x³ + 3·x² + 2·x + x² + 3·x + 2 = x³ + 4·x² + 5·x + 2
(f·g)(x) = x³ + 4·x² + 5·x + 2
5x=25
Because negative 3y and positive 3y got cancelled